MENINGKATKAN KETERAMPILAN DAUR ULANG MELALUI PEMBELAJARAN BERBASIS PROYEK PADA SMPN 3 GUNUNGSITOLI ALO’OA - Zega, Sertiwika; Laoli, Eka Septianti; Lahagu, Arianto; Lase, Asali (Yayasan Amanah Nur Aman, 2025)
The waste problem at UPTD SMP Negeri 3 Gunungsitoli Alo’oa has a serious impact on students’ learning comfort, such as disrupted concentration, decreased motivation, and the creation of an unconducive classroom environment. This study aims to determine the improvement of students’ abilities in creating recycled products through the implementation of the Project-Based Learning (PjBL) model. This is a Classroom Action Research (CAR) conducted in two cycles using a qualitative approach, employing observation techniques to evaluate the learning process, student activities, and final products. The results show that the teacher’s ability to apply the PjBL model increased from 60.83% (fair) in the first cycle to 90.83% (excellent) in the second cycle. Student activity also improved from 64.72% to 86.33%. Students’ ability to produce recycled products increased from an average learning outcome of 59.46% (57.14% mastery) to 74.64% (71.42% mastery) in the second cycle. These results indicate that the implementation of PjBL can enhance student ability and participation in Integrated Social Studies learning in class VII-1.